Preparation of mesoporous TiO2 by sol-gel and hydrothermal methods - Lazau Carmen; Orha Corina; Ursu Daniel; Nicolaescu Mircea; Vajda Melinda; International Symposium on Analytical and Environmental Problems (24.) (2018) (Szeged) (2018)
Over the last years, there has been increasing interest in the application of TiO2 with nanosized powders or mesoporous structure for gas sensing, photocatalysts, photoelectrodes, and solar energy conversion. In these applications, the control of morphology, particle size, distribution, phase composition, and porosity of TiO2 is a primary factor in determining the properties of the final materials. Mesoporous TiO2 has a large surface area because of its confined porous structure and high surface to volume ratio, and also it should have a higher photocatalytic activity, because of the improved access to the active sites of TiO2 [1]. To prepare TiO2 mesoporous nanoparticles, is not such a simple work, because the raw materials, obtaining materials conditions such as the temperature, stirring rate, ionic strength, acidity, reactant ratios, and the temperature calcination influence their formation. Mesoporous TiO2 nanoparticles can be prepared through a few methods, like hydrothermal synthesis, evaporation-induced self assembly, precipitation reaction, or the sol–gel process [2]. In this study, we report the preparation and characterization mesoporous TiO2 by sol-gel and hydrothermal methods using hexadecylamine and Pluronic 127 like surfactant-template. The materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and BET.